Comparison of different process strategies for bioethanol production from Eucheuma cottonii: An economic study. (January 2016) - Tan, Inn Shi; Lee, Keat Teong
Highlights: Red macroalgae Eucheuma cottonii was used as feedstock for bioethanol production. A combined chemical and enzymatic process is more effective than other hydrolysis schemes. A techno-economic evaluation shows the feasibility of the process. Abstract: The aim of this work was to evaluate the efficacy of red macroalgae Eucheuma cottonii (EC) as feedstock for third-generation bioethanol production. Dowex (TM) Dr-G8 was explored as a potential solid catalyst to hydrolyzed carbohydrates from EC or macroalgae extract (ME) and pretreatment of macroalgae cellulosic residue (MCR), to fermentable sugars prior to fermentation process. The highest total sugars were produced at 98.7 g/L when 16% of the ME was treated under the optimum conditions of solid acid hydrolysis (8% (w/v) Dowex (TM) Dr-G8, 120 °C, 1 h) and 2% pretreated MCR (P-MCR) treated by enzymatic hydrolysis (pH 4.8, 50 °C, 30 h). A two-stream process resulted in 11.6 g/L of bioethanol from the fermentation of ME hydrolysates and 11.7 g/L from prehydrolysis and simultaneous saccharification and fermentation of P-MCR. The fixed price of bioethanol obtained from the EC is competitive with that obtained from other feedstocks.